Fairy ponies: unicorn prince - Davidson, Zanna; Bongini, Barbara (Usborne Publishing Ltd : [distributor] HarperCollins Distribution Services : [distributor] HarperCollins Publishers Pty Ltd : [distributor] Harper Entertainment Distribution Services : [distributor] Wild Dog Press London, 2014)
A Pony Princess, Rosabel, has come to stay on Pony Island, and Puck and Holly are given the task of looking after her. But spoilt and determined, Princess Rosabel flies to the Dark Forest where she is kidnapped by Shadow. The Usborne Reading Programme is a collection of over 250 reading books, graded in seven levels. Developed with reading experts, this series now features original fiction to provide readers with even more choice. Series Three books are for fully confident readers who still need to gain the stamina needed for standard length books. They use advanced sentence structure and vocabulary and have more complex plots with subplots